First record of culex (Melanoconion) pilosus from Córdoba City, Argentina - Pires, Diego Ariel (2009)
Larvae of Culex (Melanoconion) pilosus were collected in February 2006 during a survey of mosquito fauna inhabiting water bodies in an urban environment in Crdoba city. This is the 1st record of the species in this locality of Argentina, the most western report of this species in the Chaco phytogeographic region.